Iron phthalocyanine on Cu(111): Coverage-dependent assembly and symmetry breaking, temperature-induced homocoupling, and modification of the adsorbate-surface interaction by annealing. - Snezhkova, Olesia; Bischoff, Felix; He, Yuanqin; Wiengarten, Alissa; Chaudhary, Shilpi; Johansson, Niclas; Schulte, Karina; Knudsen, Jan; Barth, Johannes V; Seufert, Knud; Auwärter, Willi; Schnadt, Joachim ; 0000-0001-9375-831X (Journal of Chemical Physics, 2016)
We have examined the geometric and electronic structures of iron phthalocyanine assemblies on a Cu(111) surface at different sub- to mono-layer coverages and the changes induced by thermal annealing at temperatures between 250 and 320 °C by scanning tunneling microscopy, x-ray photoelectron spectroscopy, and x-ray absorption spectroscopy. The symmetry breaking observed in scanning tunneling microscopy images is found to be coverage dependent and to persist upon annealing. Further, we find that annealing to temperatures between 300 and 320 °C leads to both desorption of iron phthalocyanine molecules from the surface and their agglomeration. We see clear evidence of temperature-induced homocoupling reactions of the iron phthalocyanine molecules following dehydrogenation of their isoindole rings, similar to what has been observed for related tetrapyrroles on transition metal surfaces. Finally, spectroscopy indicates a modified substrate-adsorbate interaction upon annealing with a shortened bond distance. This finding could potentially explain a changed reactivity of Cu-supported iron phthalocyanine in comparison to that of the pristine compound.